An Investigation of the Financial Management Practices of the Mosques In The Special Region of Yogyakarta Province, Indonesia - Muhammad Akhyar Adnan (Sharia Economics Converence, 2013)
This study is trying to investigate the financial management of the Masjid (Mosques) in the Special Region of Yogyakarta Province. Three main issues were focused: the amount of cash flow which include the balances on hand; the application of transparency and accountability principles in financial matters, and sound practice of financial management which include budgeting, strategic formulation and performance evaluation. The study is an exploratory in nature. There are 287 Mosques as listed weekly by Kedaulatan Rakyat Newspaper. 50 Mosques have been selected as the samples. Each county /city is represented by 10 Mosques, selected using purposive sampling method. The simple descriptive analysis is conducted on the data collected. Based on the data analysis, the study found that there is a significant cash flow of those selected samples, dominated by Infaq / Sodaqoh. Few Mosques recognized that they also receive the Zakat and Waqaf fund. The study also found that generally the Mosque Management have applied the principles of transparency and accountability in the form recording, although their skill in doing so needs to be improved. However, a significant number of Mosques Management have not yet set the periodic budget, as well as strategic formulation to realize the budget and its evaluation.